A facile aptamer-based sensing strategy for dopamine through the fluorescence resonance energy transfer between rhodamine B and gold nanoparticles. (December 2015) - Xu, Jingyue; Li, Ying; Wang, Luokai; Huang, Yanjun; Liu, Danlei; Sun, Rui; Luo, Jialin; Sun, Chunyan
Abstract: A facile aptamer-based sensing strategy was developed for dopamine through the fluorescence resonance energy transfer (FRET) between rhodamine B (RB) and gold nanoparticles (AuNPs). The different affinities of unbound and bound aptamers toward AuNPs were employed to modulate the FRET efficiency for signal transfer. Dopamine-binding aptamers (DBA) could protect AuNPs from salt-induced aggregation, resulting in the fluorescence quenching of RB via FRET. Specific binding of DBA with dopamine formed the structured complex, losing the capability to stabilize AuNPs, thus the salt-induced aggregation of AuNPs led to the decrease of fluorescence quenching ability. Correspondingly, the fluorescence intensity of RB recovered along with the dopamine concentration ranging from 26 to 2.90 × 10 3 nM with the detection limit of 2 nM. This method was successfully applied for dopamine determination in swine feeds and chicken livers. Owing to its high sensitivity, excellent selectivity and convenient procedure, this strategy will provide a promising alternative for dopamine screening. Graphical abstract: A facile and sensitive strategy was developed for fluorescent assay of dopamine based on the specific recognition of aptamers and the highly efficient fluorescence resonance energy transfer (FRET) between rhodamine B (RB) and citrate-stabilized Au nanoparticles (AuNPs). The different affinities of unbound and bound aptamers toward AuNPs were employed to modulate the FRET efficiency for signal transfer in the system. Highlights: An aptamer-based assay for dopamine was established via FRET between RB and AuNPs. The assay is convenient and easy to operate without modification of AuNPs or aptamer. The assay shows outstanding sensitivity, selectivity and application potential.